2016
DOI: 10.1080/21645515.2016.1204501
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and protective efficacy of rotavirus VP8*fused to cholera toxin B subunit in a mouse model

Abstract: In attempts to develop recombinant subunit vaccines against rotavirus disease, it was previously shown that the N-terminal truncated VP8* protein, VP8-1 (aa26-231), is a good vaccine candidate when used for immunization in combination with Freund's adjuvant. However, this protein stimulated only weak immune response when aluminum hydroxide was used as an adjuvant. In this study, the nontoxic B subunit of cholera toxin (CTB) was employed as intra-molecular adjuvant to improve the immunogenicity of VP8-1. Both, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…VP8* is the glycan-binding domain of rotavirus spike protein VP[4] that interacts with host glycan receptors as the first step of a rotavirus infection. Thus, VP8* serves as a key target for rotavirus vaccine development [ 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. When the P-VP8* proteins are expressed using the bacterial ( Escherichia coli, BL21 strain) system, the P 24 -VP8* nanoparticles assemble spontaneously [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…VP8* is the glycan-binding domain of rotavirus spike protein VP[4] that interacts with host glycan receptors as the first step of a rotavirus infection. Thus, VP8* serves as a key target for rotavirus vaccine development [ 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. When the P-VP8* proteins are expressed using the bacterial ( Escherichia coli, BL21 strain) system, the P 24 -VP8* nanoparticles assemble spontaneously [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, studies showed that the affinity of CTxB to GM1 receptors, acts as delivering moiety to the cell surface, thus increases cellular uptake efficiency and antigen presentation [29]. Secondly, the proper stability of this protein, which can even be administered orally, will increase overall protein stability [30,31]. It should be noted that the adjuvant itself, is an antigen of Vibrio cholera, so it can also induce immunization against Vibrio cholera [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Because the N-terminus of CTB contains the GM1–ganglioside-binding residues, and N-terminus of VP8-1 extends from globular domain and N-terminus is flexible domain of VP8-1. Thereby, it is plausible that the binding activity, antigenicity and conformation of the antigens were disrupted more in VP8-1–CTB compared with in CTB–VP8-1 ( 68 ). Similarly, for CTB–C-CPE, the N-terminus of CTB and C-terminus of C-CPE are important for their binding to their respective receptors ( 36 39 ).…”
Section: Discussionmentioning
confidence: 99%